Marijuana use–induced spontaneous pneumomediastinum. Issue 2 (4th March 2021) - Motes, Arunee; Laoveeravat, Passisd; Thongtan, Thanita; Nugent, Kenneth; Islam, Sameer; Islam, Ebtesam
Abstract: The presence of air in the mediastinum is a rare finding called pneumomediastinum. Spontaneous pneumomediastinum is typically benign. Marijuana use has been rarely reported to cause pneumomediastinum. Our case series presents two young men with no significant past medical history who had a history of marijuana use and developed pneumomediastinum after multiple episodes of intractable vomiting. The pathophysiology of spontaneous pneumomediastinum in marijuana users includes cyclic vomiting or microperforation of the esophagus or barotrauma during breathing maneuvers. Most cases can be managed conservatively.